2010
DOI: 10.1002/eji.201040604
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐induced TRAIL‐independent cell death in DNase II−/− embryos

Abstract: The chromosomal DNA of apoptotic cells and the nuclear DNA expelled from erythroid precursors is cleaved by DNase II in lysosomes after the cells or nuclei are engulfed by macrophages. DNase II À/À embryos suffer from lethal anemia due to IFN-b produced in the macrophages carrying undigested DNA. Here, we show that Type I IFN induced a caspasedependent cell death in human epithelial cells that were transformed to express a high level of IFN type I receptor. During this death process, a set of genes was strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…It was suggested previously that increased caspase-8 and decreased cFLIP levels are sufficient to induce apoptosis independent of death ligands (38,39). Examination of the relative amounts of caspase-8 upon interferon treatment showed an increase in caspase-8 protein levels from 8 h onwards, reaching a maximum of ϳ4-fold the basal level at 48 h (Fig.…”
Section: Ifn-induced Apoptosis Is Death Ligand Independentmentioning
confidence: 61%
See 2 more Smart Citations
“…It was suggested previously that increased caspase-8 and decreased cFLIP levels are sufficient to induce apoptosis independent of death ligands (38,39). Examination of the relative amounts of caspase-8 upon interferon treatment showed an increase in caspase-8 protein levels from 8 h onwards, reaching a maximum of ϳ4-fold the basal level at 48 h (Fig.…”
Section: Ifn-induced Apoptosis Is Death Ligand Independentmentioning
confidence: 61%
“…Several previous studies reported apoptosis induction by cFLIP silencing on the DISC, without the involvement of an external ligand (38,39). Of particular interest is previous work by Wilson et al (39), who demonstrated that a higher expression level of procaspase-8 or silencing of cFLIP is sufficient to induce apoptosis with an involvement of the DR5 receptor but without external death ligand.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…1E and 4D). This partial abrogation might be due to the insufficient ability of the Ab to neutralize the TRAIL activity, or alternatively, there could be TRAIL-independent mechanisms as recently reported in the mechanism for IFN-induced apoptosis [42]. DNase II-deficient embryos die in utero due to severe anemia caused by IFN-β produced in the macrophages carrying undigested DNA.…”
Section: Discussionmentioning
confidence: 92%
“…DNase II-deficient embryos die in utero due to severe anemia caused by IFN-β produced in the macrophages carrying undigested DNA. Although a high level of TRAIL mRNA was found in the fetal liver, a null mutation in TRAIL failed to rescue the lethal anemia, indicating that TRAIL is not necessary for inducing the apoptosis of erythroid cells in DNase II-deficient embryos [42]. Further studies are necessary to clarify the molecular mechanisms underlying IL-27 and poly(I:C)–mediated inhibition of tumor growth in TRAIL-dependent and -independent manners.…”
Section: Discussionmentioning
confidence: 99%